Adsorption of normal pentane on the surface of rutile. Experimental results and simulations - Prates Ramalho, João Paulo (2008)
Adsorption isotherms and differential heats of normal pentane adsorption on microcrystalline rutile were measured at 303 K. The heat of adsorption of n-pentane on rutile at zero occupancy is 64 kJ/mol. The differential heats have three descending segments, corresponding to the adsorption of n-pentane on three types of surfaces. At low coverage (first segment), the adsorption is restricted to the rows A of the (110) faces along the 5-fold coordinatively unsaturated (cus) Ti4+ ions with differential heat showing a linear decrease with increasing occupancy. The second segment is attributed to bonding with atoms of the rows along the remaining faces exposed, (101) and (100). The third segment is related to a multilayer adsorption. The mean molar adsorption entropy of n-pentane is ca. -25 J/mol K less than the entropy of the bulk liquid, thus revealing a hindered state of motion of the n-pentane molecules on the surface of rutile. Simulations of the adsorption of n-pentane on the three most abundant crystallographic faces of rutile were also performed. The adsorption isotherm obtained from the combination of each face's isotherm weighted by the respective abundance was found to be in a good agreement with the experimental data. A structural characterization of n-pentane near the surface was also conducted, and it was found that the substrate, especially for the (110) face, strongly perturbs the distribution of n-pentane conformations, compared to those found for the gas phase. Adsorbed molecules are predominantly oriented with their long axes and their backbone zigzag planes parallel to the surface and are also characterized by fewer gauche conformations than observed in the bulk phase.